Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Sidenreng Rappang - Nur Azizah; Andi Sri Kumala Putri. P; Mifta Farid Salam (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to determine whether there is an influence between work discipline on employee performance at the Personnel and Human Resources Development Agency of Sidenreng Rappang Regency. The population in this study were all employees at the Personnel and Human Resources Development Agency of Sidenreng Rappang Regency, totaling 45 employees, and the sampling technique used was saturated sampling. Data obtained from primary data and secondary data. The data collection techniques used are observation, questionnaires and documentation. The method used in this research is an associative quantitative research method. Based on the results of the analysis that has been carried out, it shows that the work discipline variable has a positive effect on employee performance at the Personnel and Human Resources Development Agency of Sidenreng Rappang Regency because the significant value of the results from the t-test (0.000) is smaller than 0.5. The magnitude of the contribution of work discipline to employee performance can be said to be significant from the analysis carried out at the Personnel and Human Resources Development Agency of Sidenreng Rappang Regency. And it is recommended that future researchers can further develop this research by adding other variables or indicators that can influence employee performance.